Frontispiece: Total Synthesis of Aspidosperma and Strychnos Alkaloids through Indole Dearomatization. Issue 38 (5th July 2019) - Saya, Jordy M.; Ruijter, Eelco; Orru, Romano V. A.
Abstract : Monoterpenoid indole alkaloids are the major class of tryptamine‐derived alkaloids found in nature. Together with their structural complexity, this has attracted great interest from synthetic organic chemists. In their Review on page 8916 ff., J. M. Saya, R. V. A. Orru, and E. Rujter discuss the syntheses of Aspidosperma and Strychnos alkaloids through dearomatization of indoles.